Integrative Value-Based Learning: Peran Pendidikan Pancasila sebagai Penggerak Pembentukan Karakter Peserta Didik Sekolah Dasar - Iir Nikmatul Fathonah; Heriyanto Heriyanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines Integrative Value-Based Learning as a framework that positions Pancasila Education as a driving force for character development among elementary school students. Using a descriptive qualitative approach, the research explores how Pancasila values are integrated through classroom learning, school culture, and co-curricular and extracurricular activities. The findings reveal that character formation becomes more effective when Pancasila values are embedded consistently across learning experiences rather than taught as isolated concepts. Teachers play a central role as facilitators of value internalization by connecting academic content with students’ daily experiences. School culture functions as a moral ecosystem that reinforces values through routines, habits, and social interactions, while extracurricular activities provide experiential spaces where values are practiced directly. The synergy among these educational components enables students to develop moral awareness, social responsibility, and civic identity from an early age. Integrative Value-Based Learning transforms Pancasila Education into a living value system that shapes students’ behavior, attitudes, and character in a sustainable manner, supporting the broader goal of nurturing responsible and value-oriented future citizens.